ANALISIS KEPATUHAN DAN PEMAHAMAN PAJAK PELAKU UMKM BERDASARKAN PP NO. 55 TAHUN 2022 PADA UMKM KOPI SINGGALANG KOTA SUNGAI PENUH - Pebtri Algazi; Azwani Aulia; Vera Amalia (STKIP Subang, 2026)
Mikro, Small, and medium Enterprises (MSMEs) are a type of business that has proven to be able to contribute and play a role in economic growth, both in developed and developing countries. Factors that influence the failure of MSMEs are none other than the lack of good business management, not conducting routine supervision in operations. Furthermore, many business actors still do not understand government regulations related to taxation, especially MSMEs such as the Singgalang Coffee MSMe in Sungai Penuh City. In this case, the government must move to intensify inclusive socialization throughout Indonesia. This aims to help business actors understand and knowledge related to tax regulations, especially in PP No. 55 Of 2022 and related to the Final Income Tax Rate Of 0,5%. The data used in this study is Qualitative data, namely descriptive data that focuses on the quality, nature, or category of an object, such as interview narratives, observation transcripts, documentation, and also subjective opinions. In this study, the author aims to determine the understanding and knowledge of MSMEs, particularly Singgalang Coffee MSMEs in Sungai Penuh City, regarding government regulation PP. No. 55 Of 2022 and the 0,5% Final Income Tax Rate.